Cover Image, Volume 173A, Number 9, September 2017. Issue 9 (17th August 2017) - Kruszka, Paul; Porras, Antonio R.; Addissie, Yonit A.; Moresco, Angélica; Medrano, Sofia; Mok, Gary T. K.; Leung, Gordon K. C.; Tekendo‐Ngongang, Cedrik; Uwineza, Annette; Thong, Meow‐Keong; Muthukumarasamy, Premala; Honey, Engela; et al.
Abstract : The cover image, by Paul Kruszka et al., is based on the Original Article Noonan Syndrome in Diverse Populations, DOI:10.1002/ajmg.a.38362 . Design Credit: Darryl Leja.